New Electromagnetic Force-Displacement Sensor - Benabdellah, Amine; Abbassi, Zakarya; Nakheli, Abdelrhani (Institute of Advanced Engineering and Science, 2016)
A new electromagnetic force-displacement sensor is presented. Its operating principle is based on the fundamental laws of electromagnetism (Faraday-Lenz law) and the mechanical properties of a spring. The active elements are two coils made by a wire of 60 Âµm in diameter. Using different wire diameters or different number of wire turns in the coil modify the intensity of the magnetic field and the sensor response. The average accuracy of the sensor is about âd=1Âµm, and as a force sensor is about âF = 1ÂµN. This sensor could be successfully used for the manufacture of several measuring instruments.